Characterization of Cu/Ag/Eu/Hydroxyapatite Composites Produced by Wet Chemical Precipitation - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2017)
In the first part of this study hydroxyapatite was prepared synthetically through classical wet precipitation, using Ca(NO3)(2).4H(2)O (calcium nitrate tetrahydrate) as calcium source and HgN2O4P as phosphate source. In the second part of the study HA compounds were prepared with different ratios (0.5, 1, 2, 5, 10 and 25 wt.%) of antibacterial materials like copper (Cu), silver (Ag) and europium (Eu), using the same wet precipitation method. The prepared pure HA material was utilized as the control group for comparison with Cu/Ag/Eu/HA composites. Studies of X-ray diffraction, FTIR spectroscopy, scanning electron microscopy, equipped with energy dispersive X-ray analysis were performed. The aim of this study was to investigate Cu/Ag/Eu/HA composites and the effect of metals on HA biomaterials, used as scaffold materials in bone disease treatment.
Keywords: HYDROXYAPATITES